2018
DOI: 10.3390/ijms19123798
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-8: A Novel Target to Overcome Resistance to Chemotherapy in Glioblastoma

Abstract: Caspase-8 was originally identified as a central player of programmed cell death triggered by death receptor stimulation. In that context, its activity is tightly regulated through several mechanisms, with the best established being the expression of FLICE-like inhibitory protein (FLIP) family proteins and the Src-dependent phosphorylation of Caspase-8 on Tyr380. Loss of apoptotic signaling is a hallmark of cancer and indeed Caspase-8 expression is often lost in tumors. This event may account not only for canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 75 publications
2
28
0
Order By: Relevance
“…The functions of caspase-8 are tightly modulated by cFLIP proteins, XIAP, and posttranslational modifications such as phosphorylation and ubiquitination. However, the significance of these mechanisms to regulate caspase-8 in cancers has to be further investigated [91].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The functions of caspase-8 are tightly modulated by cFLIP proteins, XIAP, and posttranslational modifications such as phosphorylation and ubiquitination. However, the significance of these mechanisms to regulate caspase-8 in cancers has to be further investigated [91].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, caspase-8 expression increases in glioblastoma, promoting sustained NFκB activation and the transcription of several cytokines. The levels of IL-8, IL-6, IL1β, CCL2, and VEGF correlate with caspase-8 expression levels, thereby painting caspase-8 as a modulator of angiogenesis and inflammation in glioblastoma [91,92].…”
Section: The Interplay Between Caspase-8 and Nfκbmentioning
confidence: 97%
“…27,28 The exogenous apoptosis pathway is initiated by Caspase-8, with its activation leading to subsequent downstream cascade reactions. 29 In the intrinsic pathway, cells triggered by intracellular stimuli through the Bcl-2 protein family activate caspase-9 and caspase-3. 30,31 In the present study, PPVI induced apoptosis in osteosarcoma cells by activating apoptosis pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we recently observed that caspase-8 expression in GBM played a non-canonical function sustaining NF-κB activation, cytokine production (i.e., IL-6, IL-8, IL-1β, MCP-1, and VEGF-α), and tumor growth in vivo [ 33 , 48 ]. Importantly, we have also reported that the aberrant activation of SRC in GBM cell lines promoted caspase-8 phosphorylation on Y380, leading to neoplastic transformation [ 49 ].…”
Section: Tumor Microenvironment and Inflammationmentioning
confidence: 99%